Visual analytics framework for multi-objective optimisation of aircraft design - Shubham, Shubham; Spinelli, Andrea; Kipouros, Timoleon (MDPI, 2026)
This paper presents a web-based visual analytics framework for robust multi-objective aircraft wing design. Aerodynamic and structural simulation data are generated for a redesigned CRM wing, with aspect ratio and skin root thickness as key variables. Ordinary Kriging surrogates are coupled with NSGA-III to explore trade-offs among lift-to-drag ratio, wing mass, and range. Input design uncertainties are propagated using Monte Carlo Simulation with Halton sampling, enabling low-cost robustness assessment. An interactive HTML–Python dashboard provides contour plots, sampled design points, and Pareto fronts, allowing engineers to perform what-if analyses and rapidly identify robust Pareto-optimal designs. Results show that a higher aspect ratio with lower skin thickness improves aerodynamic efficiency and range, while structural constraints and uncertainty bounds define feasible regions. The Kriging surrogate achieves a Surrogate Speed-Up Index (SSI) of 𝒪(10^3), offering comparable insight into wing mass, range, and 𝐿/𝐷 at roughly three-orders-of-magnitude-lower computational cost than direct mid-fidelity simulations.
Keywords: visual analytics; multi-disciplinary; multi-objective optimisation; aerodynamics; structures; aircraft wing; web-based architecture